Numerical assessment of the mean power production of a combined wind and wave energy platform - Soulard, Thomas; Babarit, Aurélien (Volume 7: Ocean Space Utilization; Ocean Renewable Energy, 2012)
Volume 7: Ocean Space Utilization; Ocean Renewable EnergyRio de Janeiro, Brazil, July 1–6, 2012Conference Sponsors: Ocean, Offshore and Arctic Engineering DivisionISBN: 978-0-7918-4494-6 International audience This paper synthesizes the performance evaluation of a hybrid ocean wave energy converter. The case of interest represents a singular approach to combine a 5MW wind turbine with floating oscillating wave surge converters (OWSCs). The first section describes the comprehensive set of equations of motion in both frequency and time domain. The mathematical and hydrodynamic assumptions are highlighted together with the numerical model. The second part starts with the assessment of the initial performance of this device, carried out on in-house simulation codes. The first stage of numerical validation is based on the linear transfer functions (RAOs) results. The analysis of these RAOs also exposes interesting mechanical properties of this particular device. Eventually, the annual average absorbed power figures are extracted from the power matrices calculated for a few different sites.